An investigation into the complex formation and potential solvent extraction of Os(IV/III) with N, N - dialkyl - N′- acyl(aroyl)thioureas - Klopper, Reynhardt (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2006.